A manutenção do território por meio da integração econômica europeia: o caso da Irlanda do Norte - Lopes, Rita de Cassia Carvalho (2024)
This thesis aims to analyse the criteria that form, organise, and maintain the territorial status of Northern Ireland, a political unit of the United Kingdom of Great Britain and Northern Ireland. This political unit, whose society is marked by segmentation, is inserted in the process of European economic integration, which has transformed the dimension of territory and borders. The choice of the theme arises from the fact that this scenario is currently undergoing the consequences of the first withdrawal of a Member State from the European Union, in the process known as Brexit. The hypothesis of this thesis is that the instruments of European economic integration are correlated with the organization and maintenance of the territory of Northern Ireland. The deductive method was used in order to analyse general concepts contained in primary sources, such as international treaties concerning the origins and formation of the Northern Irish territory, as well as the treaties and norms of European economic integration. Given the particularities of Northern Ireland and the transformations resulting from economic globalisation in the designation of territory as a marker of the international system, it was necessary to add interdisciplinary studies to International Economic Relations Law. The results indicate that it is political criteria that form the territory. They are progressively connected with economic globalisation as organizing criteria for the territory, intensely coexisting with the concept of space. It is also clear that it is the aspects related to the stages of European economic integration, i.e. customs union rules and the European common market for goods, that provide the additional criteria that organize and maintain the territory in Northern Ireland, especially as they are effective in maintaining the Irish land border friction-free and preventing a resurgence of the historic conflict over the territory.